2020
DOI: 10.1017/s1355617720000259
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Contact Frequency with Friends and with Family, Activity Engagement, and Cognitive Functioning

Abstract: Objectives: Social engagement may be an important protective resource for cognitive aging. Some evidence suggests that time spent with friends may be more beneficial for cognition than time spent with family. Because maintaining friendships has been demonstrated to require more active maintenance and engagement in shared activities, activity engagement may be one underlying pathway that explains the distinct associations between contact frequency with friends versus family and cognition. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 57 publications
4
24
1
Order By: Relevance
“…For example, in a cross-sectional study of Swiss older adults, higher engagement in leisure activities mediated the association between a higher number of close friends and higher cognitive functioning ( Ihle et al., 2018 ). Similarly, evidence from a longitudinal study of U.S. adults showed that higher contact frequency with friends, but not family, was associated with higher engagement in cognitive and physical activities, both of which were associated with higher episodic memory and executive functioning ( Sharifian et al., 2020 ). This pattern of findings has also been demonstrated when examining socioemotional outcomes.…”
Section: Differentiation Based On Relationship Typementioning
confidence: 99%
“…For example, in a cross-sectional study of Swiss older adults, higher engagement in leisure activities mediated the association between a higher number of close friends and higher cognitive functioning ( Ihle et al., 2018 ). Similarly, evidence from a longitudinal study of U.S. adults showed that higher contact frequency with friends, but not family, was associated with higher engagement in cognitive and physical activities, both of which were associated with higher episodic memory and executive functioning ( Sharifian et al., 2020 ). This pattern of findings has also been demonstrated when examining socioemotional outcomes.…”
Section: Differentiation Based On Relationship Typementioning
confidence: 99%
“…Friendships may be particularly beneficial for cognitive aging because they require more active maintenance (i.e., communication and shared activities) than family relationships, which can be more obligatory (Roberts & Dunbar, 2011. Indeed, data from the Survey of Midlife in the United States indicate that the greater engagement in cognitively stimulating leisure activities mediated the positive association between contact frequency with friends and subsequent changes in both episodic memory and executive functioning (Sharifian et al, 2020a). In addition, friendships have been shown to provide a greater source of immediate joy (Larson, Mannell, & Zuzanek, 1986) and a greater sense of companionship (Huxhold, Miche, & Schüz, 2014) than family relationships for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has consistently demonstrated that cognitively stimulating activities ( Akbaraly et al, 2009 ; Rebok et al, 2014 ) and social engagement ( Jao et al, 2018 ; Litwin & Shaul, 2019 ; Litwin & Stoeckel, 2016 ; Sharifian et al, 2020 ) have been linked to improved cognition and behavioral health outcomes in older adults. When older adults are faced with situations in which they are required to socially isolate (e.g., due to medical conditions or during pandemics, such as COVID-19 outbreak in 2019–2020), adequate social engagement, and cognitive stimulation may become rather limited, as the elderly constitute a vulnerable group during outbreaks of infectious disease and are often required to self-isolate to protect their health.…”
Section: Clinical and Practical Implicationsmentioning
confidence: 99%
“…These applications may allow older adults to socially engage with their families and friends without increasing the risk of transmission of an infectious disease. Given the benefits of continued social engagement to older adults’ mental health and cognition (e.g., Jao et al, 2018 ; Sharifian et al, 2020 ), it is recommended that they regularly engage with loved ones through technology in times of social distancing.…”
Section: Clinical and Practical Implicationsmentioning
confidence: 99%